Membrane targeting of the yeast exocyst complex - Pleskot, Roman; Cwiklik, Lukasz; Jungwirth, Pavel; Žárský, Viktor; Potocký, Martin (Biochimica et biophysica acta, 2015)
The exocytosis is a process of fusion of secretory vesicles with plasma membrane, which plays a prominent role in many crucial cellular processes, e.g. secretion of neurotransmitters, cytokinesis or yeast budding. Prior to the SNARE-mediated fusion, the initial contact of secretory vesicle with the target membrane is mediated by an evolutionary conserved vesicle tethering protein complex, the exocyst. In all eukaryotic cells, the exocyst is composed of eight subunits - Sec5, Sec6, Sec8, Sec10, Sec15, Exo84 and two membrane-targeting landmark subunits Sec3 and Exo70, which have been described to directly interact with phosphatidylinositol (4,5)-bisphosphate (PIP2) of the plasma membrane. In this work, we utilized coarse-grained molecular dynamics simulations to elucidate structural details of the interaction of yeast Sec3p and Exo70p with lipid bilayers containing PIP2. We found that PIP2 is coordinated by the positively charged pocket of N-terminal part of Sec3p, which folds into unique Pleckstrin homology domain. Conversely, Exo70p interacts with the lipid bilayer by several binding sites distributed along the structure of this exocyst subunit. Moreover, we observed that the interaction of Exo70p with the membrane causes clustering of PIP2 in the adjacent leaflet. We further revealed that PIP2 is required for the correct positioning of small GTPase Rho1p, a direct Sec3p interactor, prior to the formation of the functional Rho1p-exocyst-membrane assembly. Our results show the critical importance of the plasma membrane pool of PIP2 for the exocyst function and suggest that specific interaction with acidic phospholipids represents an ancestral mechanism for the exocyst regulation.
Keywords: kinetika; Saccharomyces cerevisiae; Exocytosis; Phosphatidylinositol (4,5)-bisphosphate; Vesicular Transport Proteins; Protein Binding; Cell Membrane; Phosphatidylinositol 4,5-Diphosphate; Exo70p; podjednotky proteinů; mutace; Saccharomyces cerevisiae Proteins; fosfatidylinositol-4,5-difosfát; Saccharomyces cerevisiae - proteiny; Molecular Dynamics Simulation; Molecular dynamics simulation; Secretory Pathway; Sec3p; exocytóza; sekreční dráha; Mutation; Rho1p; rho GTP-Binding Proteins; vazba proteinů; Rho proteiny vázající GTP; Kinetics; Protein Subunits; buněčná membrána; simulace molekulární dynamiky; The exocyst complex; vezikulární transportní proteiny